2018
DOI: 10.1016/j.exger.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent validation of the OMNI-Resistance Exercise Scale of perceived exertion with elastic bands in the elderly

Abstract: A strong positive and linear relationship was observed between the rating of perceived exertion and both heart rate and applied force. The OMNI-RES scale with elastic bands demonstrated to be a valid method for assessing the perceived exertion during resistance exercises and consequently represent a useful tool for prescribing exercise intensity to the elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 35 publications
0
39
0
3
Order By: Relevance
“…Immediately after each set, perceived exertion (RPE) was determined using a modified Borg scale ( Buckley and Borg, 2011 ). This method of assessing perceived exertion during resistance exercises is comparable to other RPE scales currently validated for monitoring intensity during resistance exercises performed with elastic bands in older populations ( Colado et al, 2020 ; Colado et al, 2018 ).…”
Section: Methodsmentioning
confidence: 86%
“…Immediately after each set, perceived exertion (RPE) was determined using a modified Borg scale ( Buckley and Borg, 2011 ). This method of assessing perceived exertion during resistance exercises is comparable to other RPE scales currently validated for monitoring intensity during resistance exercises performed with elastic bands in older populations ( Colado et al, 2020 ; Colado et al, 2018 ).…”
Section: Methodsmentioning
confidence: 86%
“…Structured program with standardized volume (12-15 repetitions * 2 sets), intra-set rest periods (1 min), frequency (twice per week) and movement cadence (3 s for both shortening and lengthening phase without rest between phases and repetitions) was applied. Training intensity ranged from 4 to 5 on OMNI Resistance for active muscle scale, which has been previously validated for older adults (Colado et al, 2018) and corresponds to 40% to 50% of 1RM (Lagally and Robertson, 2006). The concept was to keep internal load throughout the study constant with the aim of quantifying low load training-effects on measured outcomes.…”
Section: Training Protocolmentioning
confidence: 99%
“…Most of the studies found in the literature that evaluated the strength exercise variables use the test of 1RM or 10RM. In the present study, we used the subjective perception of effort through the OMNI-RES scale 27,28 , which is reproducible in a sedentary population and in elderly women 29 to determine the 1RM load and the intensity used in the experimental sessions. This scale is an instrument of easy application and low cost that has been widely used and validated to indicate a perceived effort to strengthen exercise 28,30 .…”
Section: Discussionmentioning
confidence: 99%
“…Determination of the loads used in the experimental sessions After familiarization sessions, it was performed two tests to determine the load used in the experimental sessions for each exercise. The intensity of the exercises was estimated by the subjective perception of effort using the OMNI-RES scale 27,28 in a mimetic one repetition maximum (1RM) test. Each participant was asked to point out on the scale their perceived effort immediately after the end of each attempt, which should correspond to the moderate intensity (5 to 7).…”
Section: Familiarization Sessionsmentioning
confidence: 99%